Morphometric and morphological characteristics of the trigeminal ganglion of rats in an experimental model of aseptic inflammation and introduced cryopreserved placenta - O.D. Danyliv; V.I. Shepitko; Ye.V. Stetsuk; N.V. Boruta (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. Diseases of the peripheral nervous system account for more than 50 % of all outpatient neurological pathology, and since inflammatory diseases are one of the main problems of medicine, it is important now to develop new methods of anti-inflammatory therapy based on the action of biologically active substances contained in natural products, as well as in many mammalian tissues, particularly in the placental tissue, which is an endocrine gland during pregnancy. Therefore, the issue of using cryopreserved placenta preparations is of great practical importance in the treatment of inflammatory processes and requires further research. The purpose of the work was to investigate the morphometric and morphological features of the trigeminal ganglion of rats in the experimental model of aseptic inflammation and the introduction of cryopreserved placenta. Materials and methods. The work was carried out on 50 sexually mature male rats. The control group consisted of 5 animals who received a single injection of physiological saline solution. Using standard research methods, paraffin blocks were made from which a series of semi-thin sections were cut and stained with hematoxylin and eosin. Histological sections were studied in a light Biorex 3 microscope with a digital camera using software adapted for research. Statistical data processing was performed using Microsoft Office Excel. Results. The morphometric study of rats from the control group revealed that the cytoplasm volume of the bodies of the trigeminal ganglion neurons was 3489.89 ± 37.59 μm3, the volume of the nucleus was 247.68 ± 4.30 μm3. In the experimental model of inflammation and introduction of cryopreserved placenta, destructive phenomena are observed until the seventh day, with marked swelling of the stroma, disruption in the structure of neurons with signs of cytoplasmic swelling, which is confirmed by the data of a morphometric study, namely a reliable increase in the cytoplasm volume by 30.78 % compared to the control group of animals (p < 0.05). After the seventh day of observation, the stimulating effect of components of the fetoplacental complex led to the acceleration of intracellular reparative processes. The change in the number of lymphoid cells had a wave-like nature, with a significant increase in the number of macrophages until the fifth day, which was 8.07 times higher than in the control group (p < 0.05) that indicated the activation of the humoral link of the immune response accelerated by the introduction of cryopreserved placenta. Conclusions. An increase in the number of mast cells was observed until the fifth day of observation, with a significant increase in their average number, which is associated with enhanced regulation of the state of the intercellular substance in response to an alterative factor. By the end of the experiment, there was a significant decrease in the average number of mast cells due to an increased regulatory effect of components of the fetoplacental complex of cryopreserved placenta.